2005
DOI: 10.1029/2004ja010824
|View full text |Cite
|
Sign up to set email alerts
|

Scaling and a Fokker‐Planck model for fluctuations in geomagnetic indices and comparison with solar wind ε as seen by Wind and ACE

Abstract: [1] The evolution of magnetospheric indices on temporal scales shorter than that of substorms is characterized by bursty, intermittent events that may arise from turbulence intrinsic to the magnetosphere or that may reflect solar wind-magnetosphere coupling. This leads to a generic problem of distinguishing between the features of the system and those of the driver. We quantify scaling properties of short-term (up to few hours) fluctuations in the geomagnetic indices AL and AU during solar minimum and maximum,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
66
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(77 citation statements)
references
References 44 publications
11
66
0
Order By: Relevance
“…2). Hnat et al (2003b) also showed the solar wind parameter vB 2 scaled for τ up to 26 h. Given we expect solar cycle variability (Pagel and Balogh, 2002;Hnat et al, 2005) and a particular turbulent regime may not end suddenly, our outer temporal scale, τ ≈9.1 h, is in basic agreement. However, Hnat et al (2002b) obtained α 0 =0.42±0.03 using bin sizes δε which decrease logarithmically with δε, and this disagrees with our initial estimate of α 0 =0.33±0.03.…”
Section: Scaling Collapse Of the Fluctuation Pdfssupporting
confidence: 57%
See 3 more Smart Citations
“…2). Hnat et al (2003b) also showed the solar wind parameter vB 2 scaled for τ up to 26 h. Given we expect solar cycle variability (Pagel and Balogh, 2002;Hnat et al, 2005) and a particular turbulent regime may not end suddenly, our outer temporal scale, τ ≈9.1 h, is in basic agreement. However, Hnat et al (2002b) obtained α 0 =0.42±0.03 using bin sizes δε which decrease logarithmically with δε, and this disagrees with our initial estimate of α 0 =0.33±0.03.…”
Section: Scaling Collapse Of the Fluctuation Pdfssupporting
confidence: 57%
“…Figure 4 illustrates how difficult it is to scale the ε parameter, and suggests caution in making direct comparisons between the absolute values of α 0 obtained for completely different data sets. However, the presence of fluctuations common to the solar wind and electrojet indices can be inferred from relative variations in the corresponding scaling parameters, such as those which depend upon solar phase (Hnat et al, 2005).…”
Section: Scaling Collapse Of the Fluctuation Pdfsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is still unclear to what extent the fluctuations in the solar wind are reflected in the fluctuations of magnetosphere-ionosphere system. Numerous studies have tried to approach this problem by using both deterministic and stochastic paradigms (Tsurutani et al, 1990;Hnat et al, 2005;Cheng et al, 2005;Pulkkinen et al, 2006).…”
Section: Introductionmentioning
confidence: 99%